Visualisasi Informasi Data Perguruan Tinggi Dengan Data Warehouse Dan Dashboard System - Hendro Poerbo Prasetiya; Meme Susilowati (Maranatha University Press, 2016)
University leaders have the responsibility to monitor all activities and make continuous measurements on the performance and quality of higher education which leads to ensure the achievement of the goals set. All this to get some of the information required, university leaders still have to do the data collection scattered beberpa information systems, either manually. It can slow down the decision making process for people who are at the manager level and above can not monitor the performance and quality of high pergutuan any time.Making college visualization of data information by using data warehouse and dashboard of the system can help university leaders in monitoring or monitoring the performance of all units in college he leads and perform measurements continuously on the performance and quality of higher education lead. Keywords: dashboard system, data warehouse, performance, Visualization of information